Spring and autumn historiography : form and hierarchy in an ancient Chinese annals - Van Auken, Newell Ann (Columbia University Press, 2023)
"The Spring and Autumn is an early Chinese register of events covering the eight to fifth centuries BCE, originating from the official state annals of Lu, the home state of Confucius. Tradition attributes the Spring and Autumn to Confucius, claiming that it employs subtle clues that convey his evaluations of its recorded events, and for over two thousand years, it was regarded as one of the most important Chinese classics. Despite its significance in China, the Spring and Autumn has been largely neglected and is poorly understood in the West, perhaps for the simple reason that its records, which are brief, impersonal, and highly formulaic, look nothing like the coded moral judgments that tradition claims them to be. The conventional interpretation of the Spring and Autumn focuses on irregularities in individual records, which may indeed have been the work of later editors. Spring and Autumn Historiography takes the opposite tack, analyzing categories of records that exhibit regular patterns with the aim of exposing the values and priorities that underlie the Spring and Autumn's formally regular core, which was likely produced by Lu record-keepers. This analysis shows that the key to the records lies not in their content but in their form: the records systematically use formal features to mark the relative importance of events, individual leaders, and states, and they reflect a deep concern with hierarchy, high position, and relative rank. Through its formulaic system of recording, the Spring and Autumn presents a Lu-centered hierarchy of individuals and states and seeks to display the exalted position of Lu and the Lu ruler at the pinnacle of this idealized hierarchy"-- Provided by publisher
Keywords: Confucius. -- Chun qiu.; Chun qiu (Confucius); China -- History -- Zhou dynasty, 1122-221 B.C. -- Historiography.; History -- Methodology.; Chine -- Histoire -- 1122-221 av. J.-C. (Dynastie des Zhou) -- Historiographie.; Histoire -- Méthodologie.; HISTORY / Asia / China; Historiography; History -- Methodology; China; 1122-221 B.C.; History